Sentiment Analysis on Social Media and Stakeholders about Negative Issues Among Islamic Boarding School Community In Indonesia - Kamal, Muhammad Rikzam; Noviyanto, Kholid; Subhan, Hadi; Afiana, Lia (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2024)
This study examines public sentiment towards Islamic boarding schools (pesantren) in Indonesia using Twitter data and interviews with pesantren stakeholders, including administrators (asatidz), students (santri), and the surrounding community. Sentiment analysis of Twitter data, collected using the hashtag #pondokpesantren in 2023, revealed that public sentiment is predominantly neutral, with fewer positive and negative opinions. The analysis, conducted using the K-Nearest Neighbors (k-NN) model, achieved 90% accuracy and an F1-Score of 89.9%, indicating reliable performance in classifying sentiment. On the other hand, interviews with pesantren stakeholders highlighted more nuanced issues, such as security concerns, educational autonomy, and disciplinary practices, which were not widely discussed on social media. The findings reveal a gap between public perceptions on Twitter, which tend to generalize pesantren issues, and stakeholders’ detailed, experience-based insights. This discrepancy underscores the need for open communication between pesantren and the public to address emerging concerns and improve pesantren’s education and security systems. By combining sentiment analysis and phenomenological interviews, this study provides a deeper understanding of public perceptions and the internal challenges faced by pesantren in Indonesia, offering valuable insights for future improvements in pesantren management and public engagement.